Protective and restorative effects of hexarelin on MPTP-induced lung injury in mice - Onur Celikoglu; Elif S. Karanfil; Ozlem Ozmen (Journal of Basic and Clinical Physiology and Pharmacology, 2026)
Abstract Objectives This study investigated the protective and therapeutic effects of hexarelin (HEX) against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced lung injury in mice by evaluating oxidative stress, IL-6–mediated inflammation, and Caspase-3–dependent apoptosis. Methods Fifty male Balb/C mice were randomly assigned to five groups (n=10): control, MPTP, PREHEX, POSTHEX, and HEX. Parkinson-like neurotoxicity was induced by a single intranasal dose of MPTP (1 mg/kg). Hexarelin (10 μg/kg, i.p.) was administered twice at 4-h intervals before or after MPTP exposure. Lung tissues were examined histopathologically using hematoxylin–eosin staining, and immunohistochemically for Caspase-3, IL-6, and SOD expression. Results MPTP caused severe pulmonary injury, including alveolar wall thickening, edema, hyperemia, and inflammatory infiltration, with increased Caspase-3 (p<0.001) and IL-6 (p=0.002) expression and reduced SOD immunoreactivity compared with controls (p<0.001). Both HEX regimens significantly reduced histopathological damage and improved immunohistochemical parameters (p<0.05). POSTHEX showed greater recovery than PREHEX, with lower apoptotic (p=0.005) and inflammatory (p=0.050) marker expression and higher SOD (p=0.007) levels. The enhanced efficacy of therapeutic post-treatment over prophylactic pretreatment is likely attributable to the active engagement of cytoprotective pathways during ongoing severe oxidative and inflammatory cascades, optimizing hexarelin’s receptor-mediated cellular rescue mechanisms. Conclusions Hexarelin demonstrated significant protective and therapeutic effects against MPTP-induced lung injury by mitigating oxidative stress, suppressing inflammation, and limiting apoptosis.